Implementasi Forward Chaining dan Certainty Factor pada Aplikasi Sistem Pakar Diagnosa Penyakit Kulit Wajah - Nuraeni, Fitri; Fitriani, Leni; Yusuf , Alifa Witri Alfahira (Jurnal Algoritma, 2025)
Facial skin diseases are not life-threatening, but they can interfere with a person's quality of life. Like people with skin diseases, they are unable to carry out normal activities because they can interfere with the comfort of themselves and others. However, to be able to diagnose skin diseases, it is necessary to have the role of a skin disease expert. Meanwhile, the existence of skin disease experts is still relatively rare and even if they exist, they usually require costs and limited service time. Therefore, this research develops a web-based expert system to help diagnose facial skin diseases by utilizing forward chaining and certainty factor methods. The system was designed using the expert system development cycle, and involved two experts in knowledge acquisition. Test results on 20 cases showed an accuracy rate of 85%. This system can be an initial diagnosis tool when specialists are not available.